3=-x-2

Simple and best practice solution for 3=-x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3=-x-2 equation:


Simplifying
3 = -1x + -2

Reorder the terms:
3 = -2 + -1x

Solving
3 = -2 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
3 + x = -2 + -1x + x

Combine like terms: -1x + x = 0
3 + x = -2 + 0
3 + x = -2

Add '-3' to each side of the equation.
3 + -3 + x = -2 + -3

Combine like terms: 3 + -3 = 0
0 + x = -2 + -3
x = -2 + -3

Combine like terms: -2 + -3 = -5
x = -5

Simplifying
x = -5

See similar equations:

| Y(4-2)=12 | | 9=-4y+6y | | 0.1x=.2(x+2) | | 85u-73u-2u-3u-4=24 | | -x^2=36-12x | | 3+g=51 | | 18/4=n | | u-(-26u)=27 | | -9(7y-8y)+12(6y-7y)= | | -2x+11+3x=4+x+7 | | 5x+15+5=180 | | 7/9+x=1/1/9 | | 91k-(-69)=-22 | | 5x^2=5x | | 91k-(-6)=-22 | | 3+9y= | | 8+5g=51 | | -6(2(-3.72)+1)-3=12(-3.72)+64 | | 23=21-u | | 17-9y=-3+26y | | (4-5i)+(-9+10i)= | | 7*6=u | | 7/9+x=1 | | 2k^2=24k-64 | | 16+5g=51 | | -5v+17v+8=-16 | | 10z-z=-1+3z-3-14 | | 7m+2(m-3)=12 | | -4r+1-4=-7 | | 3(-7x+3)=198 | | 3+3y=1 | | -4(z-15)=-16 |

Equations solver categories